A abstinência voluntária do consumo de carne pode ser compreendida como um princípio ético? - Marta Luciane Fischer; Andressa Luiza Cordeiro; Rafael Falvo Librelato (Ciências Sociais Unisinos)
This article discusses the relationship between the social concern with the cruelty to animals and voluntary abstinence from meat consumption. Through a quantitative evaluation of scientific texts and conceptions of citizens, this study brings a reflection guided by different views about the factors that promote that consumption, often implying a vulnerability that requires the incorporation of new paradigms leading to conscious choices about the reality involved in the system of animal production. Although the diet is based on numerous biopsychosocial factors, the access to information, especially regarding scientific knowledge about animal consciousness, added to the consolidation of bioethics, contributes to the strengthening of a critical awareness about the treatment of animals, and potentially constitutes a stimulus for the decision to abstain from meat consumption. Vegetarianism, in its various expressions, does not always represent simply a nourishment habit, but a change of conduct aimed at a better interaction with nature, regardless of the academic area of training. Such a change can go beyond the aspect of animal welfare, reaching other spheres of abuse of subjects vulnerable to economic interests. Thus, changing ethical conceptions requires a rational decision that should be performed by consolidated ethical principles and intermediated by a dialogue promoted by sciences such as Environmental Bioethics, which proposes to mediate complex, globalized and plural issues to seek consensual solutions for all involved in this and in the future generations.